Analisis Faktor-Faktor yang Memengaruhi Kepuasan Pasien Disabilitas Fisik di Unit Fisioterapi RSI Jakarta Pondok Kopi - Putri, Linda Wahyuni; Purnamawati, Dewi; Permatasari, Tria Astika Endah; Ernyasih, Ernyasih; Sepriyanti, Yuke (Indonesian of Health Information Management Journal (INOHIM), 2025)
Abstract Patient satisfaction is one indicator of a hospital's success in providing optimal services. As many as 33% of patients with physical disabilities stated that they were not satisfied with the comfort in the waiting room of the physiotherapy unit and as many as 20% admitted that the physiotherapist was not responsive to patient questions. This study was conducted to analyze the factors that affect the satisfaction of patients with physical disabilities in the physiotherapy of RSI Jakarta Pondok Kopi. This study used a cross-sectional approach and purposive sampling technique with a total sample of 120 patients with physical disabilities who received health services at the physiotherapy unit of RSI Jakarta Pondok Kopi. Self-reported questionnaires are used to collect demographic characteristic data. The patient perception questionnaire on physiotherapist skills was developed referring to the Physiotherapist Competency Standard. Patient satisfaction was measured using the Bahasa Indonesia version of the questionnaire from Measuring Patient Satisfaction with Physical Therapy Care (MRPS/MedRisk). The majority of patients with physical disabilities are ≥ 65 years old (50.83%), female (63.3%), high school education background (49.17%), unemployed (80.8%), have insurance (97.5), and have low income (75%). There is no relationship between age, gender, education, occupation, income, and insurance to the satisfaction of patients with physical disabilities. There was a relationship between patients' perception of physiotherapist skills (p = 0.011; OR: 5,045; 95%CI : 1,450-17,561) with satisfaction of patients with physical disabilities after being controlled by education and income. The factor that affects the satisfaction of patients with physical disabilities is the patient's perception of the physiotherapist's skills after being controlled by education and income. Keyword: satisfaction factors, patient satisfaction, physical disability, physiotherapy Abstrak Kepuasan pasien merupakan salah satu indikator kesuksesan rumah sakit dalam memberikan layanan yang optimal. Sebanyak 33% pasien disabilitas fisik menyatakan kurang puas terhadap kenyamanan di ruang tunggu unit fisioterapi serta sebanyak 20% mengaku terapis tidak responsif terhadap pertanyaan pasien. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi kepuasan pasien disabilitas fisik di unit fisioterapi RSI Jakarta Pondok Kopi. Penelitian ini menggunakan pendekatan cross-sectional, teknik sampling yang digunakan yaitu purposive sampling dengan total sampel 120 pasien disabilitas fisik yang memperoleh layanan kesehatan di unit fisioterapi RSI Jakarta Pondok Kopi. Kuesioner yang dilaporkan sendiri digunakan untuk mengumpulkan data karakteristik demografi. Kuesioner persepsi pasien terhadap keterampilan fisioterapis dikembangkan sendiri dengan merujuk pada Standar Kompetensi Fisioterapis. Kepuasan pasien diukur menggunakan kuesioner versi Bahasa Indonesia dari Measuring Patient Satisfaction with Physical Therapy Care (MRPS/MedRisk). Mayoritas pasien disabilitas fisik berusia ≥ 65 tahun (50,8%), berjenis kelamin perempuan (63,3%), latar belakang pendidikan SLTA (49,2%), tidak bekerja (80,8%), memiliki asuransi (97,5), dan memiliki pendapatan yang rendah (75,0%). Tidak ada hubungan antara usia, jenis kelamin, pendidikan, pekerjaan, pendapatan, dan asuransi terhadap kepuasan pasien disabilitas fisik. Ada hubungan antara persepsi pasien terhadap keterampilan fisioterapis (p = 0,01; OR: 5,05; 95%CI : 1,45-17,56) dengan kepuasan pasien disabilitas fisik setelah dikontrol oleh pendidikan dan pendapatan. Faktor yang memengaruhi kepuasan pasien disabilitas fisik adalah persepsi pasien terhadap keterampilan fisioterapis setelah dikontrol oleh pendidikan dan pendapatan. Kata Kunci: faktor-faktor kepuasan, kepuasan pasien, disabilitas fisik, fisioterapi